Bodies, doings, and gendered ideals in Swedish graffiti (Sociologisk Forskning, 2017)
Drawing from extensive fieldwork among graffiti writers in Sweden this article investigates gendered identity work and its consequences. It points to how potentially inclusive aspects of disembodied subcultural performances—that identities are negotiated through the material representation of the writer rather than on basis of the physical body—nevertheless work excludingly, especially so in terms of gender. This is so because identity work in graffiti revolves around a re-embodiment of identities through normative notions of the able, male and invisible body.
Keywords: gender; identity work; graffiti